Genomic Insights into the Radiation-Resistant Capability of Sphingomonas qomolangmaensis S5-59T and Sphingomonas glaciei S8-45T, Two Novel Bacteria from the North Slope of Mount Everest - Yang Liu; Xiaowen Cui; Ruiqi Yang; Yiyang Zhang; Yeteng Xu; Guangxiu Liu; Binglin Zhang; Jinxiu Wang; Xinyue Wang; Wei Zhang; Tuo Chen; Gaosen Zhang (Microorganisms, 2022)
Mount Everest provides natural advantages to finding radiation-resistant extremophiles that are functionally mechanistic and possess commercial significance. (1) Background: Two bacterial strains, designated S5-59T and S8-45T, were isolated from moraine samples collected from the north slope of Mount Everest at altitudes of 5700m and 5100m above sea level. (2) Methods: The present study investigated the polyphasic features and genomic characteristics of S5-59T and S8-45T. (3) Results: The major fatty acids and the predominant respiratory menaquinone of S5-59T and S8-45T were summed as feature 3 (comprising C16:1 ω6c and/or C16:1 ω7c) and ubiquinone-10 (Q-10). Phylogenetic analyses based on 16S rRNA sequences and average nucleotide identity values among these two strains and their reference type strains were below the species demarcation thresholds of 98.65% and 95%. Strains S5-59T and S8-45T harbored great radiation resistance. The genomic analyses showed that DNA damage repair genes, such as mutL, mutS, radA, radC, recF, recN, etc., were present in the S5-59T and S8-45T strains. Additionally, strain S5-59T possessed more genes related to DNA protection proteins. The pan-genome analysis and horizontal gene transfers revealed that strains of Sphingomonas had a consistently homologous genetic evolutionary radiation resistance. Moreover, enzymatic antioxidative proteins also served critical roles in converting ROS into harmless molecules that resulted in resistance to radiation. Further, pigments and carotenoids such as zeaxanthin and alkylresorcinols of the non-enzymatic antioxidative system were also predicted to protect them from radiation. (4) Conclusions: Type strains S5-59T (=JCM 35564T =GDMCC 1.3193T) and S8-45T (=JCM 34749T =GDMCC 1.2715T) represent two novel species of the genus Sphingomonas with the proposed name Sphingomonas qomolangmaensis sp. nov. and Sphingomonas glaciei sp. nov. The type strains, S5-59T and S8-45T, were assessed in a deeply genomic study of their radiation-resistant mechanisms and this thus resulted in a further understanding of their greater potential application for the development of anti-radiation protective drugs.